Islamic Corporate Governance, Audit Quality and Islamic Banking Growth - Vita Intan Safitri; Ratna Mappanyukki (Eduvest - Journal of Universal Studies, 2026)
This study aims to analyze the influence of Islamic Corporate Governance (ICG) on the growth of Islamic banking in Indonesia, with audit quality as a moderating variable. ICG in this study is measured through three main components: the Audit Committee (AC), the Sharia Supervisory Board (SSB), and the Board of Directors (BOD). This research is motivated by the need to strengthen governance and transparency in the Islamic banking system, which still has a relatively small market share compared to conventional banking. This study uses an explanatory quantitative approach with secondary data obtained from the annual reports of twelve Islamic commercial banks in Indonesia during the period 2018–2022. Data analysis was conducted using Moderated Regression Analysis (MRA) with the help of EViews software to test the direct and moderating effects of audit quality on the relationship between ICG and Islamic banking growth. The results of the study indicate that Islamic Corporate Governance (ICG) as measured by the Audit Committee , the size of the Sharia Supervisory Board (SSB), and the Board of Directors (BOD) on the growth of Islamic banking in Indonesia. In addition, this study also examines the role of audit quality as a moderating variable. The data used are secondary data from the annual reports of Islamic Commercial Banks (BUS) registered with the Financial Services Authority (OJK) during the 2018–2022 period with a purposive sampling technique . The analysis was conducted using Moderated Regression Analysis (MRA) with the help of the EViews application.